ANALISIS PERATURAN DAERAH DITINJAU DENGAN TEKNIK PENYUSUNAN PERATURAN PERUNDANG-UNDANGAN (Studi Di Provinsi Kalimantan Barat) - ODILO KELEBIT TITE,SH A.2021131035, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACTThis thesis discusses the analysis of local regulations are reviewed by the engineering drafting legislation "(studies in the province of West Kalimantan). From the results of this thesis can be concluded that the construction of regional regulations in West Kalimantan Province as opposed to the technique of preparation of legislation occurs in the system preparation and formulation of words / phrases, sentences in the title, opening, position forming local regulations, the preamble, by law, the dictum, torso, general provisions, the material is set, the formulation of the criminal provisions, the transitional provisions, and provisions cover, as well as disagreement on the cover, even in substance the regional regulation in the Articles of certain problematic of the substance of legislation higher.That regional regulations exist in West Kalimantan Province as opposed to the technique of preparation of legislation remain in place for formal legally Regional Regulation remains valid because it is formed, defined by regulatory authorities and has been promulgated in the Regional Gazette, but in substance the provisions contrary with legislation of higher void. Still the implementation of the Regional Regulation is problematic due to several factors, among others, Human Resources (HR) personnel who spearhead / leading sector forming regional regulations mastered design techniques Regional Regulation / legal drafter is still low, the level of awareness and attention of observers and investigators problem Regulations undangandalam establishment of Regional Regulation is still low and the lack of budget allocated in the formation of regional regulation.This thesis discusses the analysis of local regulations are reviewed by the engineering drafting legislation "(studies in the province of West Kalimantan). From the results of this thesis can be concluded that the construction of regional regulations in West Kalimantan Province as opposed to the technique of preparation of legislation occurs in the system preparation and formulation of words / phrases, sentences in the title, opening, position forming local regulations, the preamble, by law, the dictum, torso, general provisions, the material is set, the formulation of the criminal provisions, the transitional provisions, and provisions cover, as well as disagreement on the cover, even in substance the regional regulation in the Articles of certain problematic of the substance of legislation higher. That regional regulations exist in West Kalimantan Province as opposed to the technique of preparation of legislation remain in place for formal legally Regional Regulation remains valid because it is formed, defined by regulatory authorities and has been promulgated in the Regional Gazette, but in substance the provisions contrary with legislation of higher void. Still the implementation of the Regional Regulation is problematic due to several factors, among others, Human Resources (HR) personnel who spearhead / leading sector forming regional regulations mastered design techniques Regional Regulation / legal drafter is still low, the level of awareness and attention of observers and investigators problem Regulations undangandalam establishment of Regional Regulation is still low and the lack of budget allocated in the formation of regional regulation. Recommendation: The need assessment / further analysis of the regional regulations in West Kalimantan province, both from the juridical aspect, sociological, philosophical, and technical drafting process and substance of the material muatanperaturan area, so after being a Regional Regulation, becoming Regional Regulation effective, not cause contradictions and problems of both aspects of Mechanical Drafting, formal and material as well as meet the needs and demands for social justice. Because the purpose of the establishment of Regional Regulation not only to the rule of law / rechmatigheid alone but also so that people know and should be implemented in order to benefit / dooelmatigheid for the community. In The Local Regulation in the province of West Kalimantan involve the participation of the wider community, especially students of law,Researcher law, legal experts from academics and designers Laws Invitation / legal drafter, because the public has the right to provide input verbal and / or written the establishment of regulatory legislation, as stipulated in Article 96, Article 98 and Article 99 of Law Number 12 Year 2011 on the establishment Regulation legislation that regional regulations have been enacted that will not be problematic.Keywords: analysis, local regulations, in terms of, preparation techniques.ABSTRAKTesis ini membahas analisis peraturan daerah ditinjau dengan teknik penyusunan peraturan perundang-undanganâ€ (studi di provinsi kalimantan barat). Dari hasil penelitian tesis ini diperoleh kesimpulan Bahwa konstruksi Peraturan Daerah yang ada di Provinsi Kalimantan Barat yang bertentangan dengan teknik Penyusunan Peraturan Perundang-undangan terjadi pada sistem Penyusunan dan perumusan kata/rasa, kalimat pada bagian judul, pembukaan, jabatan pembentuk peraturan daerah, konsideran, dasar hukum, diktum, batang tubuh,ketentuan umum, materi yang diatur, rumusanketentuan pidana, ketentuan peralihan, danketentuan penutup, serta pertentangan pada penutup, bahkan secara substansi Peraturan Daerah tersebut dalam Pasal-Pasal tertentu bermasalah dari materi muatan Peraturan Perundang-undangan yang lebih tinggi. Bahwa Peraturan Daerah yang ada di Provinsi Kalimantan Barat yang bertentangan dengan teknik Penyusunan Peraturan Perundang-undangan tetap diterapkan karena secara legal formal Peraturan Daerah tetap sah karena dibentuk, ditetapkan oleh lembaga yang berwenang dan telah diundangkan dalam Lembaran Daerah, namun secara substansi ketentuan-ketentuan bertentangan dengan Peraturan Perundang-undangan yang lebih tinggi batal demi hukum. Masih diterapkannya Peraturan Daerah yang bermasalah tersebut disebabkan beberapa faktor antara lain Sumber Daya Manusia (SDM) aparatur yang menjadi ujung tombak /leading sector pembentuk Peraturan Daerah yang menguasai teknik perancangan Peraturan Daerah/legal drafter masih rendah, tingkat kesadaran dan perhatian Para pemerhati dan peneliti masalah Perundang-undangan dalam Pembentukan Peraturan Daerah masih rendah serta kurangnya Anggaran yang dialokasikan dalam pembentukan Peraturan Daerah. Rekomendasi : Perlunya pengkajian/analisis lebih lanjut terhadap Peraturan Daerah yang ada di Provinsi Kalimantan Barat, baik dari aspek yuridis, sosiologis, filosofis,dan teknik penyusunan serta substansi materi muatanperaturan daerah, agar setelah menjadi Peraturan Daerah, menjadi Peraturan Daerah yang efektif, tidak menimbulkan pertentangan dan permasalahan baik dari aspek Teknik Penyusunan, formil dan materil serta memenuhi kebutuhan dan rasa keadilan masyarakat. Karena tujuan dari dibentuknya Peraturan Daerah tidak hanya untuk kepastian hukum/rechmatigheid saja akan tetapi juga agar masyarakat tahu dan harus dilaksanakan dengan tujuan untuk kemanfaatan/dooel matigheid bagi masyarakat . Dalam Perancangan Peraturan Daerah yang ada di Provinsi Kalimantan Barat melibatkan peran serta masyarakat luas terutama para pemerhati masalah hukum, Peneliti hukum, para ahli hokum dari Akademisi dan para perancang Peraturan perundang Undangan/legal drafter, karena masyarakat berhak memberikan masukan secara lisan dan/atau tertulis dalam pembentukan peraturan Perundang-undangan, sebagaimana diatur dalam ketentuan Pasal 96, Pasal 98 dan Pasal 99 Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-Undangan agar Peraturan Daerah yang telah diundangkan tersebut nantinya tidak bermasalah.Kata Kunci :Analisis, Peraturan Daerah, Ditinjau Dari, Teknik Penyusunan.